Exploring the role of geography on reward crowdfunding - Hu, Jianwei (2021)
The reward crowdfunding has been a flourishing industry ever since its beginning as it enables the entrepreneurs to finance their businesses or ideas directly from the crowd without traditional financial intermediaries. Each investor only has to contribute a bit of money in return for a reward of a product or specific service. This thesis examines how geography affects the successful fundraising in reward crowdfunding and what factors, international intensity, social network and collaborative leadership have an impact on this process. The empirical research is based on the 24,100 worldwide Kickstarter reward crowdfunding campaigns in the technology sector from 2009 to 2019. The relevant information regarding the large-scale campaigns is scraped directly from the Kickstarter website, an international crowdfunding platform. The first empirical chapter investigates how home region orientation and international intensity will impact funding success of crowdfunding projects from the regional perspective. This paper explores whether the international reward crowdfunding campaigns are effective in attracting global backers by testing the market penetration level across the globe, and explores the economic mechanisms through which home region orientation affects funding success. The market coverage in terms of breadth and depth across the broad triad is analyzed. Empirical evidence indicates that although international reward crowdfunding is a novel form of international business and cross-border entrepreneur financing, it is still regional by nature due to home-region-bound campaign specific advantages. The influence of home region orientation of technology crowdfunding campaigns over the fundraising performance is also captured by its moderation effect on the multinationality-performance relationship. This study adds new insights to the literature on regional strategy by researching into a number of international crowdfunding projects, demonstrating that even in the digital era, the cross-border investment barriers still exist. The second empirical chapter reports a study of whether financial technology corrects home bias on Kickstarter from the perspective of country. Prior research documents the well-known home bias in traditional financial market, which shows that investors tend to invest in the assets of their home country. However, so far little empirical evidence has been given to the impact of emerging financial technology (Fintech) on the home bias correction. Using a large dataset of 21,391 technology reward crowdfunding campaigns from the Kickstarter platform, we examine whether investors exhibit a home bias in the fast-growing worldwide crowdfunding market. Our results show that, with all else being equal, campaigns attracting a higher proportion of home country investors tend to have higher probabilities of being successfully funded. Further investigation indicates that platform social networking helps to manage the crowdfunders in an effective way, and thus helps to mitigate the impact of home bias on funding success. Based on these findings, this paper reveals the positive but limited role of Fintech in alleviating cross-border barriers such as home bias effect, especially in developing countries. The final empirical chapter researches into the geographical role in crowdfunding success from the perspective of diversification and reports mediating effects of investor heterogeneity on the relationship between collaborative leadership and performance outcomes of technology crowdfunding. The findings of this paper provide supports to explain the mechanism of how the improvement of platform social networking lessons the home bias effect and increases the funding outcome. This study explores whether the exhibition of the collaborative leadership by the entrepreneurs and leading investors fosters better fundraising performance of technology crowdfunding on Kickstarter, and whether investor heterogeneity account for this relationship. Based on the 21,391 worldwide technology campaigns posted on Kickstarter between 2009 and 2019, the result reveals that the efforts of the entrepreneurs in posting updates together with the practice of leading investors in making comments leads to greater performance of technology crowdfunding, with investor heterogeneity mediates such effects. In conclusion, the propensity of people investing regionally and within home country have not been eliminated as it was supposed to be on reward crowdfunding platforms. The information asymmetry and information costs still play a vital role in this industry. Fintech could partially remove this geographic bias by effectively managing the platform social networking (leading investor leadership) and entrepreneurial leadership, which improves funding success through increasing the investor heterogeneity. Overall, the creators should focus on the needs of the local customers to take advantage of the home bias effect and simultaneously managing the before end updates and comments to enjoy the benefits of diversification.